(3GdTaGA aj GdefWbs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3jHOC HaUd ai GdJfHjg s
(3BNQgG (B:s
(3jfJgi HaUd ai GdNdjaI hGdEeGe hhLhH WGYJgG hGdETGQI Edi GdSjGSGJ hGdeYGedGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1055s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdadSaI hGdefWbs